0.3x^2+0.4x^2-0.2x^2=

Question

Asked 5/12/2013 10:09:47 PM

Updated 5/27/2014 9:17:37 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [5/27/2014 9:14:28 AM]

shifa saleheen|Points 9966|

Question

Asked 5/12/2013 10:09:47 PM

Updated 5/27/2014 9:17:37 AM

2 Answers/Comments

This conversation has been flagged as incorrect.

Flagged by yeswey [5/27/2014 9:14:28 AM]

Rating

3

0.3x^2+0.4x^2-0.2x^2

= 0.7x^2-0.2x^2

= 0.5x^2

= 0.7x^2-0.2x^2

= 0.5x^2

Added 5/27/2014 9:14:12 AM

This answer has been confirmed as correct and helpful.

Confirmed by andrewpallarca [5/27/2014 9:16:12 AM]

3

2x-y=6 rearranging the equation we can get:

y = 2x - 6 (equation 1)

7x-3y=22 (equation 2)

using equation 1 to substitute y in the equation 2 the result is:

7x - 3(2x - 6) = 22

7x - 6x + 18 = 22

x = 22 - 18 = 4

y = 2(4) - 6 = 2

The solution for the system 2x-y=6 7x-3y=22 is (4, 2)

y = 2x - 6 (equation 1)

7x-3y=22 (equation 2)

using equation 1 to substitute y in the equation 2 the result is:

7x - 3(2x - 6) = 22

7x - 6x + 18 = 22

x = 22 - 18 = 4

y = 2(4) - 6 = 2

The solution for the system 2x-y=6 7x-3y=22 is (4, 2)

Added 5/27/2014 9:17:37 AM

This answer has been confirmed as correct and helpful.

Confirmed by jeifunk [5/27/2014 9:20:06 AM], Unconfirmed by jeifunk [5/27/2014 9:28:53 AM], Confirmed by andrewpallarca [5/27/2014 11:47:02 AM]

27,955,218

questions answered

There are no comments.